"Och ett päron mognar i skuggan": Thelonious Monk i svenska medier 1948–63 - Bjerstedt, Sven (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2024)
Following the record company Blue Note’s publicity campaign for jazz pianist Thelonious Monk in 1948, the image of Monk commonly presented in Swedish as well as American media was one of an eccentric, mysterious, even weird musician, sometimes viewed as a genius. This article presents and discusses the development of the Swedish media image of Monk during the period 1948–63, from the first mentions of him in Swedish press until his second concert performance in Stockholm. The presentation includes an overview of epithets commonly associated with Monk in Swedish media; a brief look at two poems on Monk; summaries of how Monk was depicted as a musician and as a human being; a presentation of the few interviews with Monk published in Sweden; and a summary of the media coverage of Monk’s Stockholm concerts in 1961 and 1963. In sum, the media image of Monk went through a process of radical development during the period: from being presented as unknown over being dismissed as bizarre and incomprehensible to being described as familiar and ‘hip’. In a concluding section, the presented material is discussed from the perspective of social constructionism.